2018
DOI: 10.3389/fchem.2018.00323
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies as a Toolbox for Biophysical and Chemical Characterization of Lipid-Based Nanotherapeutics

Abstract: The goal of this study is to provide tools to minimize trial-and-error in the development of novel lipid-based nanotherapeutics, in favor of a rational design process. For this purpose, we present case-study examples of biophysical assays that help addressing issues of lipid-based nanotherapeutics' profiling and assist in the design of lipid nanocarriers for therapeutic usage. The assays presented are rooted in spectroscopic methods (steady-state and time-resolved fluorescence; UV-Vis derivative spectroscopy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 61 publications
1
41
0
Order By: Relevance
“…In addition, understanding the formulation targets as well as the barriers they impose is of major importance and may dictate new approaches in the formulation development process, such as drug–membrane interaction studies. These are also of use in providing better knowledge of the drugs and guiding the development of formulation [29,35].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, understanding the formulation targets as well as the barriers they impose is of major importance and may dictate new approaches in the formulation development process, such as drug–membrane interaction studies. These are also of use in providing better knowledge of the drugs and guiding the development of formulation [29,35].…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of possible changes in the microviscosity of the liposomal formulation upon drug encapsulation was also required, as it is a helpful parameter to be considered in the choice of the most adequate formulation. For example, if including the drug in the liposomal formulation alters considerably its microviscosity, it can result in the liposomal system becoming too fluid to carry the drug during the required time after administration, and the lipid composition should perhaps be revised to convey more rigid domains [29]. Microviscosity changes induced by TDF encapsulation in lipid formulations of different fluidity (DMPC, DPPC, DSPC) were further evaluated by determining T m (main phase transition temperature at which the liposomes undergo conformational changes from the gel phase to the fluid phase) and B (cooperativity of the phase transition, which provides evidences if the drug is homogeneously distributed).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25][26][27][28][29][30] In our previous works, as well as in other studies, it is reported the correlations between the biological action and cytotoxicity of drugs and their biophysical effects in biomimetic membranes, eg by altering lipid membrane packing, decreasing lipid membrane transition temperatures or disturbing cooperativity of lipid unit cells, with consequent membrane biophysical impairment. 21,[26][27][28]31,32 Additionally, several interesting reports 19,20,[33][34][35][36][37] highlighted the importance of biomimetic models based on lipid nanosystems (liposomes, monolayers and supported lipid bilayers) to acquire molecular and functional information. The aim is using this acquired information to support the development of new drugs with better selectivity and reduced side effects 34 .…”
Section: Introductionmentioning
confidence: 99%
“…21,[26][27][28]31,32 Additionally, several interesting reports 19,20,[33][34][35][36][37] highlighted the importance of biomimetic models based on lipid nanosystems (liposomes, monolayers and supported lipid bilayers) to acquire molecular and functional information. The aim is using this acquired information to support the development of new drugs with better selectivity and reduced side effects 34 . This information can also assist to the design of new chemical entities with improved efficacy and reduced toxicity, 19,34,37 or even to understand the interaction of drug delivery nanosystems with biomembranes.…”
Section: Introductionmentioning
confidence: 99%